Examining Specialization Among Sex Offenders Released From Prison. (April 2016) - Lin, Jeffrey; Simon, Walter
A prevailing cultural stereotype about sex offenders is that they tend to specialize in sexual offending. Many recent policy developments—mainly aimed to restrict the liberties of sex offenders—are rooted in this idea. We examined the correctional and arrest records of a sample of 312 sex offenders released on parole in Colorado to determine the prevalence of sexual specialization among these offenders, and to compare the legal and social characteristics of specialists and versatile sex offenders. Overall we found that very few participants officially classified as sex offenders fit the specialist stereotype. Study participants generally displayed versatile histories of criminal offending. We also found that specialists were distinguishable from versatile offenders on certain indices of social integration and mental health, and they were more likely to have had a history of offending against children.